Implementasi Pendidikan Karakter Dalam Pembelajaran PPKN Untuk Mengembangkan Nalar Kritis Pada Siswa Kelas VIII-E Di SMPN 17 Malang - Didik Iswahyudi; Romadhon Romadhon; Elisabeth Renalti Jamba (International Forum of Researchers and Lecturers, 2023)
The importance of this research is that there are important things that must be considered in this research, namely, in order to achieve the expected educational goals, quality and effective learning is needed. Based on the background that has been described, the author formulates the problem as follows: 1. What are the values ​​of character education in PPKn learning to develop critical reasoning in class VIII-E students at SMPN 17 Malang, 2. What are the obstacles in implementing PPKn learning? to develop critical reasoning in class VIII-E students at SMPN 17 Malang,3. How to implement character education in PPKn learning to develop critical reasoning in class VIII-E students at SMPN 17 Malang. The aim of this research is to find out school policies regarding the implementation of character education in PPKn learning to develop critical reasoning at SMPN 17 Malang. This research uses descriptive qualitative. The data collection techniques used are observation, interviews and documentation, data analysis techniques use triangulation to obtain the validity of the data, while the data analysis used in the research is reduction, display and verification.